TOPIC MODELLING APPLICATION FOR DETERMINING COMPETITIVENESS FACTORS OF THE SMALL BUSINESS FIRMS - Muhammad Masyhuri (International Journal of Economy, Education and Entrepreneurship, 2022)
The purpose of this study is to identify the most important competitive factors for small business development. The Mallet software topic modelling tool was used to select the ten most important topics. Three major external factors contributed most to this competitiveness, namely industry conditions and learning organisations (topic 5),  the market environment in terms of local and international opportunities (topic 7), and the understanding of entrepreneurship and entrepreneurial networks (topic 4).